Meta-Analysis of Ethnomathematics Based Geometry Learning in Indonesian Junior High Schools - Maryo Sopater Istia; Jeinne Mumu; Lala Kumala Dewi Matunubun (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the effectiveness of the ethnomathematics approach in improving the understanding of geometry among junior high school students in Indonesia. The research method used meta-analysis of six quasi-experimental articles published between 2021 and 2025 that met the following criteria: (1) used a pretest–posttest design with a control group, (2) involved junior high school students as subjects, and (3) reported quantitative data in the form of means, standard deviations, and sample sizes. The effect size was calculated using the Standardized Mean Difference (Cohen's d) and combined with a random effects model. The synthesis results showed a combined effect size of d = 0.999 (p = 0.014), which is classified as a large effect according to Cohen. The heterogeneity test resulted in Q = 48.739 (df = 5; p = 0.014) and I² = 89.74%, indicating significant variation between studies. The funnel plot analysis and Egger's test (p = 0.556) showed no significant publication bias. These results prove that the integration of cultural artifacts such as batik motifs, traditional houses, and traditional games in geometry learning is effective in improving junior high school students' mathematical understanding. This study emphasizes the importance of applying ethnomathematics as a contextual learning strategy in line with the principles of the Merdeka Curriculum.